Pengaruh Terapi Benar Pada Burnout Akademik Siswa di SMP N 2 Turi Yogyakarta - Hidayati, Rizqi Wahyu; Rafli, Raja (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Jenderal Achmad Yani Yogyakarta, 2023)
Background: Students experience both physical and psychological changes, such as burnout academic, depression, and stress. It decreases motivation, physical and emotional exhaustion, difficulty concentrating, and decreased performance. Furthermore, relaxation therapy, Benar Therapy, is needed to reduce academy burnout. Objective: This research aims to determine whether the effect of Benar Therapy can reduce the academic burnout in student of SMPN 2 Turi, Yogyakarta. Methods: The research method used was quantitative experimental design with Quasi Experimental Design Pretest Posttest Control. This research was conducted at SMPN 2 Turi, Yogyakarta in June. The research sample consisted of VIII grade students, totaling 60 samples selected using purposive sampling technique. The data were collected using a questionnaire before-and-after the intervention of benar treatment therapy. The data analysis used were univariate analysis and bivariate analysis with the Shapiro-Wilk test and T-test. Results: The Academy burnout average in the control group before the treatment was 50.37 ± 5.41, while after the treatment was at the average of 48.90 ± 4.90. In the intervention group with the benar therapy, the academy burnout before treatment showed an average of 50.80 ± 7.11, whereas after the treatment, the average academy burnout decreased to 44.60 ± 9.15. The results of the T-test show that in the control group, there is no significant correlation between treatment and academy burnout (p=0.276), while in the intervention group with benar therapy, there is a significant correlation (p=0.005). Conclusion: The results of the T-test show that in the control group, there is no significant correlation between treatment and academy burnout, while in the intervention group with benar therapy, there is a significant correlation.